A Sand Cone Model of Lean Implementation - Yestemessov, Azamat (2011)
Over the past 20 years Lean Production system has been a focus of researches by different academicians. A numerous works have been written in the field of Lean implementation in manufacturing companies. However, as shown, most of the academic topics relate to the issues of implementing Lean tools and techniques. Critical Success Factors have been also described widely; however, no efforts in systematization have been made. Only several works have a focus on integration of Lean implementation and organizational change process. Nevertheless, even those researches are found to be lacking of practical applicability. The main drawback of presented approaches is inability to capture relationship between different tools and soft dimensions of Lean during implementation process. This paper takes focus on balanced approach during Lean implementation. Through utilization of Critical Success Factors, author identifies the relationship between Lean tools, Performance-management system, and Mind-set of employees. Moreover, the research suggests the cumulative of way in relationship between these elements. The paper elaborates on similarity of Lean implementation actions and Sand Cone model of performance improvement. Further, the suitability of this approach is tested with case study in Air CA. A case study was conducted in service environment in order to fill the gap in literature on Lean implementation in service. As the result show, the relationships between organizational changes areas indeed follow the suggested principle. However, a more in-depth study in multiple cases is required.